Designing PAS (Passive Active Structure) Application based on an Android for Eleventh Grade Students of SMA Islam AT- Taufiq Diwek Jombang - Afidah, Nurul; Nugraha, Rizky Aditya; Nur, Luluk Choirun Nisak (JoEMS (Journal of Education and Management Studies), 2022)
This research aims at designing PAS (Passive Active Structure) based on an Android Application in Grammar lesson for 11th-grade students of AT- Taufiq Islamic Senior High School, Diwek, Jombang. The research used Research and Development method (R&D) that the researcher adapted from ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Taken from the data on the development phase, the researcher obtained a result of 100% points on media validation that was categorized as “good quality”. The result of material validation is 70,8% points that were also classified as “good quality”. Moreover, in the implementation phase, the student's responses were 76,8% that could be classified as "good quality". From the data that this research showed, it can be said that this application is feasible and capable of being applied to Islamic Senior High School.